Energy Audit of Thermal Power Plant - Singh, Paljinder (My University, 2013)
The rate of exploitation of the energy resources has been expanding over time and may result in reduction of panic reserves. Efficiency of all resources is crucial both in an environmental and economic sense. Using energy inadequately creates waste in all the world’s economies. It has environmental impacts with regional, local and global implications. Today, provided continues with the enlarged use of renewable resources and also restricted use of non-renewable resources. The key object is to adopt energy management in every field in order to reduce the wastage of energy sources and cost effectiveness without affecting productivity and growth. Energy audits help to recognize the pattern of energy, form of energy consumption and amount of energy consumption so that identify the possible area of energy conservation. The load distribution or consumption patterns in the power plant and the operation of energy intensive equipments or systems were studied during the energy audit in order to identify potential areas where energy saving is practically possible.
M.E.
Keywords: thermal plant; boiler efficiency; energy audit; air preheater